2023
DOI: 10.1002/ece3.10181
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic analysis of Siraitia grosvenorii in subtropical China provides insights into the origin of cultivated monk fruit and conservation of genetic resources

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Through the study of Siraitia grosvenorii plant cultivation using plant bioreactor, proliferation rate, shoot length, fresh and dry weight Indications of proliferation rate, shoot length, fresh weight, and dry weight showed that the total biomass of roselle cultivated in plant bioreactor was significantly higher than in solid and liquid cultivation (Shivani et al, 2021). The reactor promoted the growth and quality of S. grosvenorii seedlings, and the natural‐like plant S. grosvenorii obtained may have a positive effect on isolated rooting and transplanting in large‐scale commercial production (Xie et al, 2023). Some researchers evaluated Vanilla planifolia in solid culture, partial submergence and plant bioreactor for shoot proliferation efficiency and found that compared to solid culture, the proliferation rate in the reactor increased by a factor of three (Yeh et al, 2021).…”
Section: The Effect Of Thz Radiation On the Growth Process Of Pinelli...mentioning
confidence: 99%
“…Through the study of Siraitia grosvenorii plant cultivation using plant bioreactor, proliferation rate, shoot length, fresh and dry weight Indications of proliferation rate, shoot length, fresh weight, and dry weight showed that the total biomass of roselle cultivated in plant bioreactor was significantly higher than in solid and liquid cultivation (Shivani et al, 2021). The reactor promoted the growth and quality of S. grosvenorii seedlings, and the natural‐like plant S. grosvenorii obtained may have a positive effect on isolated rooting and transplanting in large‐scale commercial production (Xie et al, 2023). Some researchers evaluated Vanilla planifolia in solid culture, partial submergence and plant bioreactor for shoot proliferation efficiency and found that compared to solid culture, the proliferation rate in the reactor increased by a factor of three (Yeh et al, 2021).…”
Section: The Effect Of Thz Radiation On the Growth Process Of Pinelli...mentioning
confidence: 99%
“…Monk fruit extract is a natural sweetener derived from the fruit of the monk fruit tree ( Siraitia grosvenorii ), also known as “Luo Han Guo” or “Lo Han Kuo” in some papers. It is believed that the monk fruit has been cultivated in massive scale exclusively in the southern part of China, mostly in the mountainous areas of Guilin of the Guangxi Province ( 1 , 2 ). After filtering out sugars such as fructose and glucose, monk fruit extract on the market is a non-nutritive sweetener that has gained popularity recently due to its sweetness and potential health benefits.…”
Section: Introductionmentioning
confidence: 99%